Bioactivity-guided isolation of antiproliferative compounds from Centaurea carduiformis DC - Yaglioglu, Ayse Sahin; Demirtas, Ibrahim; Goren, Nezhun (ELSEVIER, 2014)
In this study, antiproliferative activity of methanol extract of Centaura carduiformis DC. subsp. carduiformis var. carduiformis DC (CC) was examined against Vero, HeLa and C6 cell lines in 1000 and 500 mu g/mL concentrations using the BrdU ELISA assay. The CC root (CCR) has the most effective antiproliferative activity. The root extract was fractionated using various solvent and determined antiproliferative activities. Two new and two known flavonoids were isolated from CC roots. The isolated known compound of 7-O-beta-D-glucopyranosyl-4 '-methylapigenin and new compound of 7-O-beta-D-6 ''-O-glucopyranosyl- 6 ''-O-beta-D-furanosylpinocembrin were isolated from the ethyl acetate fractions. However, wogonin and new compound of N-(pentyloxy(m-tolyl) methyl) acetamideisowogonin were obtained from chloroform fractions. The chemical structures of pure compounds were elucidated with different chemical and spectroscopic methods (IR, H-1 NMR, C-13 NMR, HETCOR, COSY, GC-MS, etc.) and their antiproliferative activities were determined against Vero, HeLa and C6 cell lines. The IC50 results showed that the compound 4 has the highest activity against Vero (250 mg/mL) and HeLa (735 mg/mL) cell lines than isolated other compounds from determined values. (C) 2014 Phytochemical Society of Europe. Published by Elsevier B.V. All rights
Keywords: Centaurea carduiformis subsp carduiformis; var. carduiformis; Flavonoids; Vero; HeLa; C6; Antiproliferative activity; SESQUITERPENE LACTONES; AERIAL PARTS; 2 FLAVONOIDS; WOGONIN; Plant Sciences; Pharmacology & Pharmacy